PARTISIPASI PENYUSUNAN ANGGARAN PADA SATUAN KERJA PERANGKAT ACEH RUMAH SAKIT UMUM dr. ZAINOEL ABIDIN BANDA ACEH - Ainul Ridha (SI-MEN, 2017)
This study aims to determine whether participation in budgeting at the Aceh Device Work Unit in General Hospital dr. Zainoel Abidin (RSUDZA) has functioned well and in accordance with applicable procedures and regulations. The population in this research is all Aceh work unit at RSUDZA. Based on the established criteria, the targeted population is selected as many as 37 people. The method of analysis used in this research is descriptive quantitative analysis, which is analyzing the descriptive hypothesis. The results of this study indicate that Participation in the drafting of the budget that run by the General Hospital dr. Zainoel Abidin in Banda Aceh has not been running optimally so that future development budget arrangements can not keep up with the challenges and development